Peningkatan Jiwa Kewirausahaan Siswa Melalui Workshop Kewirausahaan dalam upaya Membentuk Generasi Mandiri di SMP PAB 23 Bandar Klippa - Sarah Salsabila Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) was implemented with the aim of fostering and enhancing the entrepreneurial spirit and skills of Junior High School (SMP) students through an Entrepreneurship Workshop at SMP PAB 23 Bandar Klippa. This program was designed using a practice-based participatory learning approach (learning by doing), which positions students as active subjects in all stages of the activity, from planning, production, to product marketing. A total of 39 seventh grade students were directly involved in this activity. Through this experiential learning process, students had the opportunity to develop creative thinking, teamwork, and problem-solving skills in a real-life setting. The evaluation results showed a significant increase in several entrepreneurial indicators, namely student self-confidence increased from 55% to 85%, communication skills from 60% to 88%, and interest in entrepreneurship from 50% to 83%. These findings prove that the practice-based learning method is effective in fostering an entrepreneurial mindset and independent character in students. Furthermore, this Community Service Program (KKN) activity demonstrates collaboration between universities and schools in implementing contextual and applicable entrepreneurship education. It also has the potential to be developed as a sustainable learning model to support the achievement of the Pancasila Student Profile, particularly in the dimensions of creativity, independence, and mutual cooperation.